The mediating role of the aesthetic experience between transformational leadership and innovation - Youngkeun Choi (Cogent Business & Management, 2019)
The purpose of this study is to examine the relationship between transformational leadership types and the motivation of software engineers. This study uses full range of leadership as a major theory and investigate how transformational leadership types influence the innovative behaviors of software developers by using a mediator of aesthetic experience. For this, this study surveys 352 software developers working at 35 companies in Korea and analyzes the data using AMOS 24. In the results, first, charisma, inspirational motivation, intellectual stimulation, and individualized consideration increase the aesthetic experience of software developers. Second, the aesthetic experience of software developers affects their innovative behaviors positively. Finally, intellectual stimulation and individualized consideration increase the innovative behaviors of software developers through their aesthetic experience. For theoretical contributions, this study has contributed to academic research by producing the empirical evidence to support the theories of leadership and the innovation of software developers and by confirming the applicability of the theory of aesthetic experience in organization research to explain users' psychological and behavioral reactions to the technological activities. For managerial implications, the managers in software development companies can understand leadership issues for motivating software developers in the perspective of aesthetic experience.
Keywords: 650; Transformational leadership; aesthetic experience; innovative behavior